Why Preserve Modern Now? - Coutinho, Bárbara (Docomomo Journal, 2012)
Coming to design in a natural development from architectural practice, Le Corbusier considered design not as a sum or addition to architecture. Its existence decisively constructed and modulated interior space, as light and shadows, materials or planes. From that belief, he quests the perfect and ideal form that asserts itself as a model of universal validity, arriving at three different furniture types: type–needs, type–furniture and human limb objects. Consequently, together with Charlotte Perriand and Pierre Jeanneret, in 1928 he drew the prototype of the Grand Confort armchair, presented the following year at the Salon d’Automne in Paris.